Presentation Style of Bedhaya Bedhah Madiun Dance in Pura Mangkunegaran - Sriyadi Sriyadi; R.M. Pramutomo (Dewa Ruci: Jurnal Pengkajian dan Penciptaan Seni, 2021)
Bedhaya Bedhah Madiun dance in Mangkunegaran is a dance repertoire Yogyakarta style that successfully has absorbed from Krida Beksa Wirama during the reign of Mangkunegara VII. Though, based on observation, the presentation style in Mangkunegaran has a significant difference from the Yogyakarta style. This article aimed to study about presentation style of Bedhaya Bedhah Madiun dance in Mangkunegaran to determine the forming of its presentation techniques. This study uses an ethnochoreology approach with archival research methods. The results showed that the style could be change as responses to challenges or problems from the sociocultural conditions. The forming of the Bedhaya Bedhah Madiun dance style in Mangkunegaran does not occur in an event but is a process. The presentation style formed because of a problem with the inheritance system so that it undergoes significant changes. The problem arises from social, political, cultural, and economic conditions. The response against those problems has to form the Bedhaya Bedhah Madiun dance characteristics in Mangkunegaran though not all were positive.